Production of cloned transgenic silkworms by breeding non-diapausing parthenogenetic strains. (July 2021) - Zabelina, Valeriya; Yonemura, Naoyuki; Uchino, Keiro; Iizuka, Tetsuya; Mochida, Yuji; Takemura, Yoko; Klymenko, Vyacheslav; Sezutsu, Hideki; Sehnal, František; Tamura, Toshiki
Graphical abstract: Highlights: Bivoltine parthenogenetic strains have been successfully established. The strains laid non-diapausing eggs when their parent eggs was developed at 15 °C. Transgenic silkworms could be created with greater ease and higher efficiency. The created silkworms have been maintained as clonal populations and cryopreserved. Abstract: Clonal transgenic silkworms are useful for the functional analysis of insect genes and for the production of recombinant proteins. Such silkworms have previously been created using an existing ameiotic parthenogenetic strain. However, the process was labor intensive, and the efficiency of producing transgenic silkworms was very low. To overcome this issue, we developed a more convenient and efficient method by breeding non-diapausing parthenogenetic strains. The strains produced non-diapausing eggs only when the embryogenesis of the parent eggs was performed at low temperatures, which could then be used for injecting vector plasmids. This demonstrated that transgenic silkworms could be produced with greater ease and efficiency. To breed the strains, we crossed the existing parthenogenetic strains with bivoltine strains and made F1 and F2 from each cross. Then we selected the silkworms whose eggs have a high ability of parthenogenesis and became non-diapausing. We also demonstrated that the germplasm could be cryopreserved in liquid nitrogen. Thus, this method increases the efficiency and ease of using genetically engineered silkworms to analyze gene function and produce recombinant proteins, potentially impacting various industries.